Childbearing, curve progression, and sexual function in women 22 years after treatment for adolescent idiopathic scoliosis: a case-control study - Danielsson, A J; Nachemson, A L (Spine (Philadelphia, Pa. 1976), 2001)
A consecutive series of female patients with adolescent idiopathic scoliosis treated between 1968 and 1977, either with distraction and fusion using Harrington rods (n = 145) or with a brace (n = 122), were followed for at least 20 years after completion of the treatment. To determine the long-term outcomes of childbearing and sexual life in women treated for adolescent idiopathic scoliosis, as compared with matched control subjects who did not have scoliosis. The effect of pregnancy on curve progression is not established, and results are contradictory. Few reports exist on the social life (marriage, childbearing, and sexual function) of formerly treated individuals with scoliosis. In this study, 136 surgically treated women (94%) and 111 brace-treated women (91%) completed the Scoliosis Research Society (SRS)/MODEM's questionnaire concerning childbearing and sexual life as a part of an unbiased personal follow-up examination. Of these, 129 surgically treated and 105 brace-treated women also underwent a radiographic examination. The Cobb method was used to measure curve size in present and earlier examinations. An age-matched control group of 90 women was randomly selected and subjected to the same examinations. The mean age for all the groups was 40 years. Of the surgically treated and brace-treated women, 85% were or had been married, as compared with 82% of the control women. In the total cohort, 628 pregnancies had occurred. No significant mean difference existed between the groups in the number of children born (1.8 for the surgically treated, 1.9 for the brace-treated, and 2 for the control women) (P = 0.25). The patients in the brace-treated group had a significantly higher mean age at first pregnancy (28 years) than the control subjects (25.9 years) (P = 0.011), whereas the age for the surgically treated women (26.6 years) did not differ significantly from that for the brace-treated women. There were no significant differences between the groups in rates for low back pain (35% for the surgically treated, 43% for the brace-treated, and 28% for the control group) or for cesarean section (19% for the surgically treated, 14% for the brace-treated, and 18% for the control group) during the first pregnancy. The rate of vacuum extractions was higher in the surgically treated group (16%) than in the control group (5%) (P = 0.036) or the brace-treated group(8%). Limitation of sexual function from the back was admitted by 33% of the surgically treated, 28% of the brace-treated, and 15% of the control women: surgically treated vs control subjects (P = 0.0042), brace-treated vs control subjects (P = 0.026), and brace-treated vs surgically treated subjects (P = 0.57, a nonsignificant difference). These limitations were largely because of difficulties participating physically in activities or self-consciousness about appearance. Pain was a minor reason for limitation. There was no correlation between progression of the major or lumbar curve and number of pregnancies, or between curve progression and age at first pregnancy. Patients treated for adolescent idiopathic scoliosis appeared to function well with regard to marital status and number of children. The scoliotic curve did not seem to increase as a result of childbearing. Minor problems occurred during pregnancy and delivery. Some patients, however, experienced a slight negative effect in their sexual life.